The Bethlehemite order rescued by Ricardo Palma’s Tradiciones peruanas - Miranda Malpartida, Agatha Alejandra (2020)
This article will deal with the story «Los Barbones». It is proposed that in this text the renowned author of the Tradiciones peruanas, Ricardo Palma, shows the presence of empirical experience related to medicine by giving an account of transcendental objectives and of summative exposition, where the memory of the name of the hospitaller order of the Bethlehemites is presumed. This religious institution, which remained in Peru for more than three hundred years, re-emerges with new vigour to extend our view of an era of common interest by bringing us the history of medicine and health of the ancient Peruvians. This connects with the current situation, as the history, healing methods and coping skills of these people can act as a core encapsulation, which would contribute to a better understanding and development of current attitudes towards COVID-19.